Risk Factors Associated with Progression to Surgery in Patients with Ischemic Colitis - Je-Seong Kim; Ho-Jin Choi; Chan-Mook Im; Ga-Ram You; Young-Eun Seo; Chae-June Lim; Hyung-Hoon Oh; Young-Eun Joo (The Korean Journal of Gastroenterology)
Background/Aims: Ischemic colitis (IC), the most common ischemic syndrome affecting the gastrointestinal tract, results from a decreased blood supply to the colon. Persistent symptoms can lead to complications, necessitating surgery. This study assessed the clinical characteristics and risk factors for poor outcomes in IC. Methods: This retrospective observational study examined the medical records of 141 patients diagnosed pathologically with IC via surgery or colonoscopy at Chonnam National University Hwasun Hospital between April 2004 and August 2023. Results: Eighteen (12.8%) and 123 (87.2%) patients were diagnosed by surgical biopsy and biopsy with colonoscopy, respectively. Multivariate analysis identified right-sided colon involvement, fever, and the absence of hematochezia as risk factors for the progression to surgery (odds ratio [OR]=5.924, 95% confidence interval [CI] 1.009–34.767, p=0.049; OR=24.139, 95% CI 5.209–111.851, p<0.001; and OR=0.076, 95% CI 0.013–0.446, p=0.004, respectively). The in-hospital mortality was 5.7% (8/141), and the patients who died exhibited higher rates of shock. The median (interquartile range) hospital stay was 11 (1–219) days. Patients who had longer hospital stays (≥14 days) had a significantly higher rate of fever but a lower rate of hematochezia. Conclusions: A multidisciplinary approach is crucial for determining the need for surgery in patients with right-sided colon involvement, fever, or the absence of hematochezia.